Perbandingan hasil BTA metode Mikroskopis (Ziehl Neelsen) dan metode Tes Cepat Molekuler (GeneXpert) pada pasien TB paru - Misyani, Misyani; Rizki, Zuriani; Rahmayanti, Rahmayanti; Safwan, Safwan (JoMLaT (Journal of Medical Laboratory Technology), 2024)
Tuberculosis is an infectious disease that most often occurs in the lungs with a percentage of 80% caused by an Acid Resistant Bacillus (BTA), namely the bacterium Mycobacterium tuberculosis. One of the priorities in controlling pulmonary TB is being able to detect TB cases early. Microscopic examination of BTA using the Ziehl Neelsen method is a widely used examination method. The current technological development that is able to detect TB quickly and accurately is the GeneXpert examination. This study aims to determine the comparison of the results of microscopic BTA examination methods (Ziehl Neelsen) and molecular rapid tests (GeneXpert) in pulmonary TB patients from sputum samples. This study uses a descriptive method that looks at the comparison of the results of BTA microscopic method (Ziehl Neelsen) and molecular rapid test (GeneXpert) from data obtained from the Laboratory of Dr. Zainoel Abidin Hospital. Samples in this study were taken as many as 26 samples. The results obtained were microscopic method (Ziehl Neelsen) and molecular rapid test (GeneXpert) were able to detect Mycobacterium tuberculosis. Based on the results of the research that has been done, it can be concluded that there is no difference between the two results obtained from the microscopic method (Ziehl Neeslsen) and molecular rapid test (GeneXpert).